The influence of grain size and triple junctions on corrosion behavior of nanocrystalline Ni and Ni-W alloy. (May 2022) - Wasekar, Nitin P.
Abstract: The present study attempts to rationalize the higher corrosion rates of nanocrystalline passivating metals in ∼3.5 wt% NaCl environment when grain size approaches below 10 nm. A simple model is proposed correlating the grain size with corrosion current utilizing the contribution from triple junctions. The higher corrosion rate below critical grain size was attributed to the presence of a high volume fraction of triple junctions demonstrating inverse Hall-Petch type (corrosion) relation. The relationship proposed reveals the application window of nanocrystalline metals demanding improved corrosion resistance. Graphical abstract: Image, graphical abstract